Simulation and Analysis of Carbon-in-Leach (CIL) Circuits - Wadnerkar, Divyamaan; Utikar, Ranjeet; Tade, Moses; Pareek, Vishnu (Elsevier, 2012)
Carbon in leach (CIL) is an important process in gold processing involving simultaneous leaching and adsorption. The process holds the key to profitability in gold extraction. While the mechanism of leaching and adsorption are well known, the effect of different operating and design parameters on the CIL circuit performance is still empirical. The focus of this paper is to study the effect of parameters like cyanide concentration, oxygen concentration and mean particle diameter on the overall efficiency of CIL circuit. A dynamic model based on first principles is developed for the entire CIL circuit. Suitable kinetic models for both leaching and adsorption are adopted from the literature. Customizable simulator is written in MATLAB to simulate the model. Simulation results are first validated using previously published results. The validated model is then used to perform sensitivity studies on different parameters that affect the gold extraction process. The model can be used for controlling the operating parameters and to optimize the CIL circuit in order to achieve higher efficiency.